IS THE ETHICS OF ECONOMIES ADAPTED OR NOT TO THE IMPERATIVE OF BIOETHICS - Dejan Donev (Human Research in Rehabilitation, 2012)
The ethics in economy is not only a corrector, but also must be initiator if we want to achieve essence of our existence - the human being as “Homo ethicus”, as well as, which is more important for mankind - to achieve a human being as “Homo homine ethica ethicus est”. This remark points on two things. First: we came to the stage where we become aware about the fact that our economies are dehumanized. The second: that’s the reason why we must return to ethics and pull out from it that universal values which will make the managers of natural recourses more ethically awarded, so they will be able to start managing production without endangering bio potentials anymore. Previous remark lead us to conclusion that, no matter if the idiom “business ethics” is oxymoron or not, the present ethics is more a list of rules of conduction or, more precisely, etiquette. This clearly points that this kind of ethics of economy and in economy is not adoptive to the imperative of Bioethics: Don’t misuse recourses if you want to feed yourself and those for which you create the existence! This is so because always when we talk about ethics and ethicizing of those which managing the base of existence, de facto, are discussions about choosing the appropriate model of capitalism. The problem of these “discussions” is that we almost always forget to explain: is the chosen model of capitalization of society applicable considering the local specifics and needs of community? Therefore, the imperative of Bioethics, in this context, is to teach the ethics how to think about bio resource and bio heritage, even if we stop talk of some kinds of ethics and ethicizing of economies and of those which managing with it, because if we reconsider the reactions of the population, it is clear that they are seek of talking about it. But also, it’s recognizable the fact that they who talks just show that the essential thinking about Bioethics is absent and that the Bioethics, de facto, is a tabby. This fear from true talking and essential declaring origins from fear that thinking about the biohumanization of economy consequently will result with change of awareness and conscience about ethics, in general.